"You come up with different theories every year": Practitioner perceptions of injury risk factors and player monitoring practices in elite men's domestic cricket. Issue 3 (June 2021) - Goggins, Luke; McKay, Carly; Peirce, Nicholas; Stokes, Keith; Williams, Sean
The aim of the current study was to capture and better understand the current perceptions of injury risk factors and player monitoring practices in elite men's domestic senior cricket, to help guide practice in this setting. A cross-sectional mixed-methods design was used, consisting of a quantitative survey sent to science and medicine practitioners at all English County clubs ( n  = 23, with representation from each club) and a set of qualitative interviews ( n  = 10 from six County clubs). Previous injury and physical fitness were the intrinsic injury risk factors most frequently endorsed as being important, with reduced recovery time and congested match schedules the most frequently endorsed extrinsic risk factors. Monitoring bowling overs was the most common tool for continually assessing injury risk. Player adherence was perceived to be the main factor impacting effective monitoring, along with human resource and practical application of monitoring knowledge. The interviews revealed that communicating value, fostering effective working relationships, and a strong club culture were important for successfully implementing monitoring and prevention initiatives. Cricket presents distinct challenges for its practitioners, and more education and guidance on appropriate monitoring methods and analysis is needed.